Private/Public in 18th-Century Scandinavia - Nauman, Sari; Vogt, Helle; Nauman, Sari; Vogt, Helle (Bloomsbury Academic)
An interdisciplinary exploration of the emerging notion of the 'private' in relation to the public in 18th-century Scandinavia.
English
Keywords: European history; Modern history to 20th century: c 1700 to c 1900; Social & cultural history; History of ideas